2014
DOI: 10.1037/a0033409
|View full text |Cite
|
Sign up to set email alerts
|

What is learned from repeated pairings? On the scope and generalizability of evaluative conditioning.

Abstract: The investigation of evaluative conditioning (EC) has been mainly concerned with the conditioning of individual stimuli. Namely, a specific conditioned stimulus (CS) is paired with a positive or negative unconditioned stimulus and consequently acquires the valence of the unconditioned stimulus. In the present article, we expand the notion of EC to CS cues (e.g., gender) as distinguished from CS objects (e.g., an individual). We developed a conditioning paradigm that allows for the simultaneous investigation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Moreover, significant generalization effects were obtained only for participants who had accurate (vs. inaccurate) CA. Different from Hütter et al (2013) , this research demonstrated generalization effects for stimuli that were not part of the conditioning procedure. However, generalization effects on the category itself were not investigated.…”
Section: Theoretical Backgroundmentioning
confidence: 52%
See 1 more Smart Citation
“…Moreover, significant generalization effects were obtained only for participants who had accurate (vs. inaccurate) CA. Different from Hütter et al (2013) , this research demonstrated generalization effects for stimuli that were not part of the conditioning procedure. However, generalization effects on the category itself were not investigated.…”
Section: Theoretical Backgroundmentioning
confidence: 52%
“… Hütter et al (2013) focused directly on the generalizability of EC effects. Specifically, they successfully distinguished evaluative identity conditioning (i.e., conditioning of an individual CS) from evaluative cue conditioning (i.e., conditioning of a cue representing a social category such as age or gender).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…When members of one group were paired with negative (or positive) images, even previously-unseen creatures that had the same object on the head, were evaluated more negatively (or positively). Thus, this study has found evidence for generalization to new stimuli, but only when participants were aware of the contingencies (i.e., remembered accurately which group of creatures was associated with which valence; for similar results, see Hütter, Kutzner, &Fiedler, 2014, andTigges, 2019). In conclusion, generalization of EC effects to new stimuli seems possible, but the available evidence largely shows that generalization is dependent on awareness (contrast Olson & Fazio, 2006; see Glaser & Kuchenbrandt, 2017, for a discussion).…”
mentioning
confidence: 53%
“…Using the present paradigm, participants might undergo an affective-priming task in which primes could be new strings that follow the positive or the negative grammar. Another approach would be to adopt process-dissociation methods, as those often used in AGL (e.g., Norman et al, 2016) and EC research (e.g., Hütter et al, 2014), and to test whether participants can voluntarily control the influence of the acquired structures.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…An evaluative conditioning (EC) paradigm could overcome this limitation. In a typical EC task, a neutral stimulus (conditioned stimulus or CS) is repeatedly paired with a positive or negative unconditioned stimulus (US), as a consequence of which the CS acquires the valence of the US (see Hofmann, De Houwer, Perugini, Baeyens & Crombez, 2010;Hütter, Kutzner & Fiedler, 2014;Spruyt, Hermans, De Houwer & Eelen, 2004). In such a paradigm, the neutral scenes could serve either as the CS to be aversively or appetitively conditioned, or as no CS controls.…”
Section: Discussionmentioning
confidence: 99%